Patient's Safety during Blood Transfusions in Hospitals Affiliated with Tehran University of Medical Sciences - N Dehghan Nayeri; Z Arab Ameri; Kh Seylani (Iran University of Medical Sciences, 2016)
Abstract Background & Aim: Blood transfusion is one of the most common procedures performed for hospitalized patients. Despite the significant contribution of these products to preserve and improve the quality of life, poor control at any stage - before, during or after the injection- can lead to complications for the patients and it can cause many risks and affect patient safety. Therefore, this study aimed to assess patient safety in the process of transfusion at the Hospitals affiliated to Tehran University of Medical sciences. Material & Methods: This study was a descriptive and observational study. The surgical wards, emergency units and ICU were randomly selected from two hospitals. The instrument of this study was a Checklist with 38 questions developed based on the guidelines for transfusion process, as well as an extensive review of published literature. The observations performed using patients' files and nurses' performances. Data analyzed by SPSS version 16. Results: The results of the study have shown that the patient safety met favorably in less than a fifth (19.2%) prior to injection and about one third during injection (32.7%). In case of side effects, the majority of subjects had desired performance (over 70%) for treat the signs and notifying the doctor. Conclusion: According to the results, it is recommended that in-service courses be taken in the transfusion process and emphasize on observing patient safety before and during injection as a protective stage for preventing from any risk and complication. In addition, it is recommended the guidelines of the transfusion process provide to nurses so that they can implement them.